Answer:
<h2>
<em><u>c</u></em></h2>
Step-by-step explanation:
6m+9q-3mq+4m= 10m + 9q - 3mq = C
0 remainder of 6
Hope this helps
Answer:g(x) is more narrow than x^2
Step-by-step explanation:the bigger the coefficient in front othe x^2 the skinny or narrow the parabola becomes our teacher would say x^2 is the parent function runs 1 mile you are 3x^2 your in 3 miles whose skinner lol
It is a function. Every x value is different.
Answer:
(x-3), 4 (x - 3)^2 (x + 3) (2 x + 7)
Step-by-step explanation:
Factor all the expressions,
1st expression= 4x^2 - 36=4(x^2-9)=4(x+3)(x-3)
2nd expression=2x^2 - 12x + 18 =2(x^2-6x+9)=2 (x - 3)^2=2(x-3)(x-3)
3rd expression=2x^2 + x - 21=(x - 3) (2 x + 7)
HCF=Commo factor=(x-3)
LCF=Common factor*Remaining factor=4(x+3)(x-3)(x-3) (2 x + 7)=4 (x - 3)^2 (x + 3) (2 x + 7)